2016
DOI: 10.3390/molecules21091184
|View full text |Cite
|
Sign up to set email alerts
|

Three Pairs of New Isopentenyl Dibenzo[b,e]oxepinone Enantiomers from Talaromyces flavus, a Wetland Soil-Derived Fungus

Abstract: Three pairs of new isopentenyl dibenzo[b,e]oxepinone enantiomers, (+)-(5S, and a new isopentenyl dibenzo [b,e]oxepinone, arugosin N (4), were isolated from a wetland soil-derived fungus Talaromyces flavus, along with two known biosyntheticallyrelated compounds 5 and 6. Among them, arugosin N (4) and 1,6,10-trihydroxy-8-methyl-2-(3-methyl-2-butenyl)-dibenz[b,e]oxepin-11(6H)-one (CAS: 160585-91-1, 5) were obtained as the tautomeric mixtures. The structures of isolated compounds were determined by detailed spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…A second 1,2,3,6tetrasubstituted benzene ring was constructed based on HMBC correlations from ortho coupled aromatic protons at δ 7.33 (1H, d, J = 8.2 Hz, H-8) to two oxygenated aromatic carbons at δ 154.5 (C-6) and 162.7 (C-10), and at δ 6.58 (1H, d, J = 8.2 Hz, H-7) to two quaternary aromatic carbons at δ 124.8 and 113.4, assigned to C-9 and C-11, respectively. These data were supportive of a dibenzo[b,e]oxepinone skeleton [20].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…A second 1,2,3,6tetrasubstituted benzene ring was constructed based on HMBC correlations from ortho coupled aromatic protons at δ 7.33 (1H, d, J = 8.2 Hz, H-8) to two oxygenated aromatic carbons at δ 154.5 (C-6) and 162.7 (C-10), and at δ 6.58 (1H, d, J = 8.2 Hz, H-7) to two quaternary aromatic carbons at δ 124.8 and 113.4, assigned to C-9 and C-11, respectively. These data were supportive of a dibenzo[b,e]oxepinone skeleton [20].…”
supporting
confidence: 58%
“…, and 119.5 (CH-15), five quaternary carbons at δ 147.0 (C-2), 138.4 (C-4), 124.8 (C-9), 113.4 (C-11), and 116.9 (C-13), three oxygenated carbons at δ 154.5 (C-6), 162.7 (C-10), and 162.4 (C-14) as well as a carbonyl and an acetal carbon at δ 197.2 (C-12) and 103.4 (C-5), respectively. These resonances suggested that compound 1 contains two-tetrasubstituted benzene rings as found in arugosin type derivatives, such as arugosin K (4)[20].…”
mentioning
confidence: 90%
“…were isolated from it. The genus Talaromyces was widely found from soil, [3] plants, [4 -5] sponges, [6] tunicate, [7] and also from lichen in our study. The second metabolites produced by Talaromyces, mainly including lactones, peptides, alkaloids, polyketides, steroids, terpenoids, and so on, [8,9] showed biological activities.…”
Section: Introductionmentioning
confidence: 54%
“…However, subsequent HPLC-CD analysis of 5 was unsuccessful, possibly due to the poor HPLC and CD behavior of the compound ( Figure S9 ). To our knowledge, fungal natural products including isopestacin, pestacin, pestalachloride A, fimetarone A, and arugosins K−M, have been reported as racemic mixtures of the S and R enantiomers [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%